Type 2 Diabetes Mellitus and Alzheimer’s Disease: Bridging the Pathophysiology and Management - Alam, Fahmida; Asiful Islam, Md.; Haryo Sasongko, Teguh; Hua Gan, Siew (Current Pharmaceutical Design, 2016)
Although type 2 diabetes mellitus (T2DM) and Alzheimer’s disease (AD) are two independent diseases, evidences from epidemiological, pathophysiological and animal studies have indicated a close pathophysiological relationship between these diseases. Due to the pathophysiological similarity of T2DM and AD, which includes insulin resistance and deficiency, protein aggregation, oxidative stress, inflammation, autophagocytosis and advanced glycation end products; AD is often referred to as “type 3 diabetes”. In addition to the targeted regimens usually used for treating T2DM and AD individually, currently, anti-diabetic drugs are successfully used to reduce the cognitive decline in AD patients. Therefore, if a common pathophysiology of T2DM and AD could be clearly determined, both diseases could be managed more efficiently, possibly by shared pharmacotherapy in addition to understanding the broader spectrum of preventive strategies. The aim of this review is to discuss the pathophysiological bridge between T2DM and AD to lay the foundation for the future treatment strategies in the management of both diseases.
Keywords: oxidative stress